THE CHALLENGE OF INTEGRATING SHARIA CRIMINAL LAW IN THE NATIONAL LEGAL SYSTEM - Gunawan Widjaja; Adrian Bima Putra (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
The integration of Sharia criminal law into the national legal system presents significant challenges. Firstly, there are fundamental differences between the principles and values espoused by Sharia criminal law and national criminal law, which may hinder their alignment. Secondly, the juridical and institutional challenges require the revision of laws and regulations, as well as the development of new mechanisms to implement the law, which requires inter-agency coordination and a significant amount of time. Thirdly, the socio-cultural aspect is also a major obstacle, given that the application of Sharia criminal law must be adapted to a society that is diverse in terms of religion, culture and social values. Thus, a thoughtful and inclusive approach, as well as effective communication and education strategies are needed to achieve harmonious integration.